Black Swan Event: Exchange Rate Impact on Jakarta Composite Index (Case Study of the Covid-19 Pandemic) - Nurma Fitrianna; Tiara Widya Antikasari; Ratna Yunita (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The Covid-19 pandemic brought economic, financial and social shocks to the world community. The emergence of this outbreak in Indonesia has made the capital market experience various challenges, especially earlier this year, which had decreased due to the emergence of the Covid-19 outbreak. No wonder the Covid-19 pandemic is likened to a black swan event for the global economy. The data analysis technique used in this study was a simple regression model. The test results prove that the exchange rate has a significant effect on the Jakarta Composite Index (JCI). The coefficient of determination was 48.4 (48.4%), which indicates that the exchange rate could explain 48.4% toward the variation of share prices during the pandemic for all companies listed on the Indonesia Stock Exchange (IDX) from March to August 2020. Meanwhile, the other 51.6% is explained by other factors which are not disclosed in this study.